Comparison of IOL power calculation and refractive outcome after laser refractive cataract surgery with a femtosecond laser versus conventional phacoemulsification - Filkorn, Tamás; Knorz, Michael C. (Journal of refractive surgery, 2012)
Journal of Refractive Surgery | PURPOSE: - To compare intraocular lens (IOL) power calculation and refractive outcome between patients who underwent laser refractive cataract surgery with a femtosecond laser and those with conventional cataract surgery. - - METHODS: - In this prospective study, 77 eyes from 77 patients underwent laser refractive cataract surgery (laser group; Alcon LenSx femtosecond laser), and conventional cataract
Gesehen am 02.10.2018